Problems Faced by Students with Intellectual Disabilities in Their Participation in Sports Education: Parent Views - Hüseyin Can İkizler; Seher Akşit; Semra Arslan; İrem Altan Aksu; Reyhan Dağ; Emine Büşra Yılmaz; Sevim Akşit (Türk Spor ve Egzersiz Dergisi)
Intellectual disability is a disorder that affects the child's daily social and practical skills. For this reason, unhealthy diet, sedentary lifestyle and physical movement limitation are the most common lifestyle problems in children with intellectual disabilities. Parents' opinions, attitudes, alexithymic conditions and social skill levels are effective in the participation of students with intellectual disabilities and other special needs in sports education. The aim of this research is to examine the problems encountered by students with intellectual disabilities in their participation in sports education in terms of parents' opinions. The study is based on the Socio-Ecological Model (SEM), one of the social model theories, as a theoretical framework. The research is a case study, one of the qualitative research approaches. In this research, the study group was reached by the maximum variation sampling method. Parents of children with intellectual disabilities in different cities of Turkey were included in the research in the 2021-2022 academic year. During the research process, three different study groups receiving special education and rehabilitation center, special lower class and inclusive education were studied. Data were collected by individual interview technique. The data obtained from all three groups were thematic analysis and analyzed by creating codes, categories and themes. As a result of the analysis of the data obtained, the findings were collected under four main themes in accordance with the theoretical framework. These are individual problems, social problems, problems caused by the physical environment and problems caused by politics. As a result of the research, it was determined that, according to the parents, the reason why their children with intellectual disabilities cannot participate in sports training is primarily due to problems arising from society. This situation can be evaluated within the exosystem and macro system according to SEM. Based on this model, which focuses on the individual and examines the effects on the individual, the two systems located at the outermost center have the greatest impact on individuals with intellectual disabilities.